2020
DOI: 10.1007/s12015-020-09961-0
|View full text |Cite
|
Sign up to set email alerts
|

Key Success Factors for Regenerative Medicine in Acquired Heart Diseases

Abstract: Stem cell therapy offers a breakthrough opportunity for the improvement of ischemic heart diseases. Numerous clinical trials and meta-analyses appear to confirm its positive but variable effects on heart function. Whereas these trials widely differed in design, cell type, source, and doses reinjected, cell injection route and timing, and type of cardiac disease, crucial key factors that may favour the success of cell therapy emerge from the review of their data. Various types of cell have been delivered. Injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 153 publications
(217 reference statements)
0
14
0
Order By: Relevance
“…Research is also being conducted on WJ-MSC in neurological diseases in young patients with cerebral palsy, autism, traumatic brain damage and hypoxic-ischemic encephalopathy. WJ-MSCs were also used in hematology (aplastic anemia, graft-versus host disease (GVHD)), cardiology (chronic coronary disease, heart failure), immunology (systemic lupus erythematosus), musculoskeletal diseases (Duchene and Becker disease) and others (including rare diseases) [99][100][101][102][103] These clinical trials do not exceed phase II. Most of them have demonstrated safety in clinical use, but minority treated efficacy as a main endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Research is also being conducted on WJ-MSC in neurological diseases in young patients with cerebral palsy, autism, traumatic brain damage and hypoxic-ischemic encephalopathy. WJ-MSCs were also used in hematology (aplastic anemia, graft-versus host disease (GVHD)), cardiology (chronic coronary disease, heart failure), immunology (systemic lupus erythematosus), musculoskeletal diseases (Duchene and Becker disease) and others (including rare diseases) [99][100][101][102][103] These clinical trials do not exceed phase II. Most of them have demonstrated safety in clinical use, but minority treated efficacy as a main endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a reduction in post-AMI major adverse cardiovascular events and an improvement in left ventricular function at 6 mo after cell injection were observed[ 39 ]. We noticed that therapeutic results of CD34+ cell implantation were dose-dependent[ 6 , 38 - 41 ]. Greater improvement was associated with higher doses with a threshold dose of over 10 million cells, particularly in the setting of myocardial infarction[ 40 , 41 ].…”
Section: Efficacy Of Cd34+ Cell Implantation In Ischemic Cardiovascular Diseasementioning
confidence: 99%
“…CD34+ cells are multipotent hematopoietic stem cells also known as endothelial progenitor cells and are useful in regenerative medicine for treating ischemic injuries[ 5 ]. These cells are easily mobilized from the bone marrow into peripheral circulation and characterized by their ability to promote neoangiogenesis and cardiomyocyte regeneration[ 6 ]. Previous published trials have reported the effectiveness of CD34+ cell implantation for treating ischemic vascular disease like ischemic stroke, peripheral limb ischemia and MI[ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Culture-expanded MSCs consist of a heterogeneous population of cells exhibiting various phenotypes and functional properties, and the extent of these properties depends on the tissue, donor, and species of origin, isolation technique, and culturing protocols ( Ankrum et al, 2014 ). Such variations are known to limit the potential of MSCs for clinical translation, and strategies to enhance engraftment are needed ( Hou et al, 2005 ; Hénon, 2020 ).…”
Section: Introductionmentioning
confidence: 99%